Identifying Mood Types Analysis in BTS’ Speech at UNICEF - Annisa Siti Harlizanti (LingPoet: Journal of Linguistics and Literary Research, 2020)
This research focuses on analysing the types of mood in BTS’ speech at UNICEF. This research has two objectives, the first one is to describe the type of mood contained in the speech and to analyze how the mood types represent the characteristics of the speech. From the analysis of interpersonal meaning through mood structures, there are 76 subjects and 71 finites. While for residue elements, there are 60 predicators, 64 complements and 96 adjuncts consisting of 16 mood adjuncts, 45 circumstantial adjuncts, and 35 conjunctive adjuncts. From the analysis of mood types, the writer found there are 64 declarative moods, 6 imperative moods and 3 interrogative moods. The most dominant mood type in the speech is declarative. The characteristic of the speech is inaugurative speech which is a speech read by influential people to formalize something that's why the speaker shows that he was more informative with the statements he said while delivering his speech.